Metabolite signatures of heart failure, sleep apnoea, their interaction, and outcomes in the community. (17th October 2021) - Dutta, Shashwati; Li, Desmond; Wang, Andy; Ishak, Mark; Cook, Kristina; Farnham, Melissa; Dissanayake, Hasthi; Cistulli, Peter; Hunyor, Imre; Liu, Renping; Wilcox, Ian; Koay, Yen Chin; et al.
Abstract: Aims: Sleep apnoea and congestive heart failure (CHF) commonly co‐exist, but their interaction is unclear. Metabolomics may clarify their interaction and relationships to outcome. Methods and results: We assayed 372 circulating metabolites and lipids in 1919 and 1524 participants of the Framingham Heart Study (FHS) (mean age 54 ± 10 years, 53% women) and Women's Health Initiative (WHI) (mean age 67 ± 7 years), respectively. We used linear and Cox regression to relate plasma concentrations of metabolites and lipids to echocardiographic parameters; CHF and its subtypes heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF); and sleep indices. Adenine dinucleotide phosphate (ADP) associated with left ventricular (LV) fractional shortening; phosphocreatine with LV wall thickness; lysosomal storage molecule sphingomyelin 18:2 with LV mass; and nicotine metabolite cotinine with time spent with an oxygen saturation less than 90% ( β  = 2.3 min, P  = 2.3 × 10 −5 ). Pro‐hypertrophic metabolite hydroxyglutarate partly mediated the association between LV wall thickness and HFpEF. Central sleep apnoea was significantly associated with HFpEF ( P  = 0.03) but not HFrEF ( P  = 0.5). There were three significant metabolite canonical variates, one of which conferred protection from cardiovascular death [hazard ratio = 0.3 (0.11, 0.81), P  = 0.02]. Conclusions: Energetic metabolites were associated with cardiac function; energy‐ and lipid‐storage metabolites with LV wall thickness and mass; plasma levels of nicotine metabolite cotinine were associated with increased time spent with a sleep oxygen saturation less than 90%, a clinically significant marker of outcome, indicating a significant hazard for smokers who have sleep apnoea.